Mobile marketing adoption by Finnish telecommunications companies in 2008-2018 - Latto, Joel (2018)
Mobile devices, mobile infrastructure and mobile services have developed in an increasing pace during 2000s and continue to do so in 2010s. With this progress, companies have started to adopt various mobile marketing technologies in order to get their messaging in the screens of old and new potential customers alike. Finnish telecommunications companies have been in the center of the mobile revolution, and therefore they make for a very interesting industry to analyze from mobile marketing technology adoption’s perspective. This research is composed of two main parts. First, a thorough literature review was conducted to gain understanding of the academic consensus of what is mobile marketing and what technologies are most often associated with it. Second, a series of semi-structured interviews were carried out with people who either were currently or had been employed by Finnish telecommunications companies between 2008 and 2018. Together with these two data sets combined, a broader picture of the evolution of mobile marketing technology adoption was made, and several key patterns in the technology adoption were recognized, that all the companies in question shared.